EFFICACY OF GnRH-PGF2alpha •GnRH, PMSG AND PMSG + hCG IN POSTPARTUM ANESTROUS CROSSBRED COWS - MUNEER, S; RAO, K SADASIVA; RAJU, K G SOLMON (The Indian Journal of Animal Reproduction, 2023)
A total of 80 Frieswal crossbred cows having history of postpartum anestrum for more than 45 days were selected. The cows were randomly divided into 4 groups. Three groups were treated with ovysynch protocol, PMSG and PMSG + hCG, and the group 4 was control group. The time interval between the treatment and estrus was 7 .00 ± 1.46, 2. 75 ± 0.23, 3.90 ± 1.17 and 16.45 ± 2.92 days in group 1, 2, 3 and 4, respectively. The Al index was 1.44, 1.71, 1.75 and 1.66, in group 1, 2, 3 and 4, respectively, and the corresponding service period was 81.33 ± 5.62 (58-158), 70.50 ± 5.24 (48-99), 73.37 ± 5.16 (49-105) and 69.50 ± 7.44 (52-98) days. The overall conception rate was 90, 70, 80 and 30 %, in group 1, 2, 3 and 4, respectively. The conception rate was higher in GnRH-PGF 2a -GnRH group than in the other groups. All the three groups were effective for induction of estrus in postpartum anestrus crossbred cows.